PRINCIPLES OF TEACHING FOREIGN LANGUAGESIN LEARNING PROCESS - Eshmirzaeva , Nozima Bakhodirovna (Educational Research in Universal Sciences, 2023)
The article is devoted to one of the most important components of learning process-learningprinciples. Learning principles is a set of rules that allows to make an educational process more efficient. The article covers some traditional and modern classificatins of principles. The analysis of modern principles of teaching foreign languages has been done here. A number of social contradictions relevant to the modern educational processare mentioned (for example, the increasing amount of disgestible information and a limited number of hours allocated for acquisition). The article is addressed to students, methodologists,teachers of foreign languages, specialistsin the field of linguistics, andanyone interested in problems of teaching foreign languages.